Pengembangan Multimedia Interaktif Menggunakan Aplikasi PowerPoint untuk Siswa Kelas V Sekolah Dasar - Musbar, Fadli; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This study aims to determine the characteristics, and level of eligibility (validity), and to determine the level of practicality (practicality) of interactive multimedia developed using PowerPoint applications. The development model used is the Multimedia Development Life Cycle (MDLC). This model has six stages, namely Concept, Design, Material Collecting, Assembly, Testing, and Distribution. This research was carried out in three schools. Respondents from this study were three PGSD UNP lecturers as validators, three homeroom teachers for class V, and 71 students of class V elementary school. The instruments used are validity questionnaires and practicality questionnaires. The data were analyzed using qualitative and quantitative descriptive analysis techniques; validity analysis and practicality analysis. This research produces interactive multimedia that is interesting, interactive, valid, and practical. The validity of the developed interactive multimedia reached a very valid category with a percentage score of 90% media validity, 92.5% material validity, and 92.5% language validity. The practicality of the interactive multimedia being developed reaches the very practical category. The practicality of the teachers achieved an average percentage score of 92.5%. The students' practicality achieved an average percentage score of 92.88%. It can be concluded that the interactive multimedia developed is very feasible and very practical for use in elementary schools.